Interlocking intramedullary nailing in fracture shaft of the femur - Haque, Md Anwarul; Hossain, MZ; Kabir, MH; Akanda, NI; Hossain, MB (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):159-64. The abstract of this article is available on the PubMed website